2023
DOI: 10.3390/nu15061328
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Childhood Cancer Survivors: Results from Southern Thailand

Abstract: There is limited information on vitamin D deficiency among childhood cancer survivors (CSS), especially in tropical countries. The aims of this study are to determine the prevalence and risk factors for vitamin D deficiency in CCSs. This study was conducted at the long-term follow-up clinic for CCSs at Prince of Songkla University, Songkhla, Thailand. All CCSs who were followed up between January 2021 and March 2022 were enrolled. Demographic data, dietary dairy intake, average weekly duration of outdoor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In survivors from a southern Thai population, Vitamin D levels were low in comparison to those of healthy Europeans and North Americans. The authors noted that the lower levels of their population might partly reflect geographic differences in Vitamin D metabolism [50]. A study systematically followed childhood cancer survivors and observed a steady decline in Vitamin D levels over the survival period.…”
Section: Discussionmentioning
confidence: 99%
“…In survivors from a southern Thai population, Vitamin D levels were low in comparison to those of healthy Europeans and North Americans. The authors noted that the lower levels of their population might partly reflect geographic differences in Vitamin D metabolism [50]. A study systematically followed childhood cancer survivors and observed a steady decline in Vitamin D levels over the survival period.…”
Section: Discussionmentioning
confidence: 99%